Preparation and characterization of solid biopolymer electrolytes based on polyvinyl alcohol/cellulose acetate blend doped with potassium carbonate (K2CO3) salt - Abubakar Abdulkadir, B. (Elsevier B.V., 2022)
Solid polymer electrolytes (SPEs) based on blended polyvinyl alcohol (PVA) and cellulose acetate (CA) incorporated with potassium carbonate (K2CO3) salt were developed in this study. The electrolytes were prepared by incorporating salts into the polymers in various weight percent (wt.) using solution casting technique. The developed electrolytes were characterized physicochemically and electrochemically using XRD, FTIR, FESEM, EIS, and LSV for crystal phase, chemical interaction, morphology, conductivity and potential window, respectively. Formation of complex between blended polymers and the salt has been established by the characterization results. The effect of PVA to CA ratio as well as the effects of salt contents on the performance of the prepared electrolytes was measured. It was found that the prepared SPE based on the polymer blend PVA:CA-80:20 (in weight) and with 20 wt salt content produced the maximum conductivity of 5.30 Ã 10-4 Scm-1. The potential window of the optimized sample was tested and shows maximum potential window of 2.84 V. Based on the observed performance, SPEs based on PVA-CA-K2CO3 complex could serve as suitable electrolyte material for energy storage devices. Â© 2022 Elsevier B.V.